Assessment of Gender Perceptions Onboard Maritime Ships: Case Study on Cruise Lines Industry - Catalin Popa; Sergiu Lupu; Filip Nistor; Andrei Bautu (Administrative Sciences)
This study explores gender perceptions and equity challenges within the maritime cruise industry, focusing specifically on crew experiences aboard European Union-flagged vessels. The research aims to evaluate the extent to which gender diversity, equality, and inclusion are perceived, practiced, and institutionalized onboard. A structured Knowledge, Attitudes, and Practices (KAP) survey was administered to the crew members across various departments and ranks, investigating perceptions of discrimination, career advancement, workplace safety, and the implementation of gender-sensitive policies. Results indicate persistent gender disparities, particularly in areas such as promotion opportunities, emotional burden, and reporting of harassment. While overall attitudes toward diversity appeared positive, a significant proportion of female respondents reported experiencing bias, isolation, and unequal treatment despite possessing equivalent qualifications. Statistical analysis, including Chi-square tests and Exploratory Factor Analysis, identified three dominant perception dimensions: structural bias, emotional strain, and safety concerns. A notable gap emerged between institutional policies and actual behaviours or trust in enforcement mechanisms. The authors contribute to the field by designing a context-specific KAP instrument, applying robust statistical methodologies, and offering actionable recommendations to maritime organizations. These include enhancing reporting systems, improving mentorship opportunities, and institutionalizing training on unconscious bias. This study provides empirical evidence to support policy reforms and cultural shifts aimed at fostering gender-inclusive environments onboard maritime cruise vessels.